The earnings of immigrants and the quality adjustment of immigrant human capital - Mesbah Sharaf (IZA Journal of Migration, 2013)
The quality dimension of immigrant human capital has received little attention in the economic assimilation literature. The objective of this paper is to demonstrate how human capital acquired in different source countries may be adjusted according to its quality in the Canadian labor market. This is achieved by deriving quality-adjustment indices using data from the 2001 Canadian census. These indices are then used to examine the role of schooling quality in explaining differential returns to schooling and over-education rates by country-of-origin. The key finding is that accounting for schooling quality virtually eliminates native-immigrant gaps in returns to schooling and the incidence of over-education. The quality of human capital is important for understanding the economic integration of immigrants.
Keywords: F22; I2; J15; J31; 330; economic integration; returns to schooling; over-education; schooling quality; human capital; immigrants